APPLICATION OF PROBLEM BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES ON MOMENTUM AND IMPULSE MATERIALS - Ravika Syarifah; Winsyahputra Ritonga (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to determine the effect of Problem Based Learning on Student Learning Outcomes in Momentum and Impulse Material in SMA Negeri 14 Medan A.Y.2018 / 2019. This study used the quasi-experimental method with the research design of two desaign pretest-posttest groups. The population of this study was all students of class X SMA 14 Medan. The sampling technique used cluster random sampling consisting of two classes with a total sample of 66 students. The instruments used were essay tests totaling 9 validated items and observation sheets for student learning activities. Analysis can be done by testing normality, homogeneity and t. The results of the study showed that there were differences in student learning outcomes taught by using problem-based learning models with a posttest average value of 76.79 compared to students who were taught with conventional learning with a posttest average value of 67.73. From these results, it can be concluded that the problem-based learning model is better used in improving student learning outcomes.Keywords: Learning Activities, Learning Outcomes, Problem Based Learning